2020
DOI: 10.1128/msphere.01008-20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Five mcr-9 -Carrying Enterobacterales Isolates in Four Czech Hospitals

Abstract: Infections caused by carbapenemase-producing bacteria have led to the revival of polymyxins as the “last-resort” antibiotic. Since 2016, several reports describing the presence of plasmid-mediated colistin resistance genes, mcr, in different host species and geographic areas were published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 27 publications
6
33
1
1
Order By: Relevance
“…In our three selected isolates, mcr-9 was demonstrated to be located on IncHI2/IncHI2A plasmids by the hybrid (Illumina-Oxford Nanopore) approach, together with other AMR genes conferring resistance to different antimicrobial classes, including the bla SHV −12 ESBL gene type detected in the two plasmids of pig origin, and different genes involved in heavy metals metabolism. Similarly, previous findings detected IncHI2-or IncHI2A-type plasmids in mcr-9 positive Enterobacteriaceae, often together with other resistance determinants (including HPCIAs) and to heavy metals mainly from human patients (Carroll et al, 2019;Chavda et al, 2019;Kieffer et al, 2019;Bitar et al, 2020;Faccone et al, 2020;Kananizadeh et al, 2020;Lin et al, 2020;Osei Sekyere et al, 2020;Soliman et al, 2020;Tsui et al, 2020;Umeda et al, 2020;Elbediwi et al, 2021;Marchetti et al, 2021;Sun et al, 2021), and also from animal (Börjesson et al, 2020;Yuan et al, 2019;Borowiak et al, 2020;Haenni et al, 2020;Leite et al, 2020), food (Borowiak et al, 2020;Sadek et al, 2020;Tyson et al, 2020), and environmental (Kamathewatta et al, 2020) sources. Few reports also described mcr-9 integrated into the chromosome of Citrobacter (Ribeiro et al, 2021) and Salmonella (Pan et al, 2020;Tyson et al, 2020) isolates, with a genetic context similar to the structure observed in mcr-9-harboring plasmid sequences, suggesting a possible mcr-9 transfer as a gene cassette between plasmids and chromosomes (Pan et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…In our three selected isolates, mcr-9 was demonstrated to be located on IncHI2/IncHI2A plasmids by the hybrid (Illumina-Oxford Nanopore) approach, together with other AMR genes conferring resistance to different antimicrobial classes, including the bla SHV −12 ESBL gene type detected in the two plasmids of pig origin, and different genes involved in heavy metals metabolism. Similarly, previous findings detected IncHI2-or IncHI2A-type plasmids in mcr-9 positive Enterobacteriaceae, often together with other resistance determinants (including HPCIAs) and to heavy metals mainly from human patients (Carroll et al, 2019;Chavda et al, 2019;Kieffer et al, 2019;Bitar et al, 2020;Faccone et al, 2020;Kananizadeh et al, 2020;Lin et al, 2020;Osei Sekyere et al, 2020;Soliman et al, 2020;Tsui et al, 2020;Umeda et al, 2020;Elbediwi et al, 2021;Marchetti et al, 2021;Sun et al, 2021), and also from animal (Börjesson et al, 2020;Yuan et al, 2019;Borowiak et al, 2020;Haenni et al, 2020;Leite et al, 2020), food (Borowiak et al, 2020;Sadek et al, 2020;Tyson et al, 2020), and environmental (Kamathewatta et al, 2020) sources. Few reports also described mcr-9 integrated into the chromosome of Citrobacter (Ribeiro et al, 2021) and Salmonella (Pan et al, 2020;Tyson et al, 2020) isolates, with a genetic context similar to the structure observed in mcr-9-harboring plasmid sequences, suggesting a possible mcr-9 transfer as a gene cassette between plasmids and chromosomes (Pan et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Comparative analysis showed that the plasmids in E. cloacae SL 264 (pSL264), S. marcescens SL267 (pSL267) and K. aerogenes SL269 (pSL269) were completely identical. This plasmid, designated pSL264, was similar to other, previously identified plasmids, including pEB-1 in E. cloacae with 98.51% identity (KX230795) [24], pACM1 in Klebsiella oxytoca with 98.51% identity (KJ541681) [25], p51929_MCR_VIM in Citrobacter freundii with 98.51% identity (CP059429) [26], and pKp616_2 in K. pneumoniae with 98.52% identity (CP026497) [27]. However, the genetic environment surrounding bla IMP-1 in pSL264 was found to be unique.…”
Section: Structure Of the Plasmid Harboring Bla Imp-1supporting
confidence: 72%
“…The reports of VIM and MCR co-production in ECC isolates are increasing, as described elsewhere [30][31][32][33][34]. The presence of mcr-9-like genes bound by two insertion sequences as in p3849_IncHI2_mcr and as reported in Sadek et al 2020 andBitar et al 2020 will not express colistin resistance and such plasmids can circulate silently until detected.…”
Section: Discussionmentioning
confidence: 81%
“…The reports of VIM and MCR co-production in ECC isolates are increasing, as described elsewhere [30][31][32][33][34]. The presence of mcr-9-like genes bound by two insertion se-…”
Section: Discussionmentioning
confidence: 96%